1993
DOI: 10.1038/bjc.1993.306
|View full text |Cite
|
Sign up to set email alerts
|

The relationship of quantitative epidermal growth factor receptor expression in non-small cell lung cancer to long term survival

Abstract: Summary Increased expression of epidermal growth factor receptor (EGFr)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
111
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 202 publications
(114 citation statements)
references
References 20 publications
3
111
0
Order By: Relevance
“…whereas still others indicated that patients with EGFR-positive tumours may survive longer than patients without EGFR expression (Dazzi et al. 1989: Veale et al. 1993.…”
Section: Discussionmentioning
confidence: 99%
“…whereas still others indicated that patients with EGFR-positive tumours may survive longer than patients without EGFR expression (Dazzi et al. 1989: Veale et al. 1993.…”
Section: Discussionmentioning
confidence: 99%
“…Nicholson et al, 10 after reviewing the literature from 1985 to 2000 regarding EGFR and cancer types association, indicated that this marker was rarely related to other clinical and prognostic markers in NSCLC. However other studies had reported a relationship between EGFR expression and patient survival, 28 as well as a relationship between this expression and tumor pathogenesis progression. 29 In our cohort, there was no statistical correlation between diffuse membranous expression of EGFR and patient survival (P40.05).…”
Section: Study Of Altered E-cad and Egfr Expressions G Deeb Et Almentioning
confidence: 96%
“…9,10 However, the checkered history of EGFR IHC may represent a challenge to broad acceptance of these tools. Initially, measurement of EGFR was performed using radioligand binding assays, 11 which were difficult to conduct and poorly reproducible. These assays were replaced by IHC as the standard method for assessment of EGFR.…”
mentioning
confidence: 99%